Indian Assigned Expatriates and Indian Students in the Host Country : The Focus on Social Supports - Habeeb Mohamed, Mag Mohamed Meeran Mohiadeen; Dvořáková, Zuzana, 1960-; Pichanič, Mikuláš, 1942-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2016)
The researcher of this study " Indian Migrants and Self-Initiated Expatriates in the host Countries: the Focus on Social Support" the whole study about the Indian expatriates who are living in the United Kingdom and the main goal of this research is to predict how successful the Indian expatriates in their settling process in the UK and the focus of social supports. The sample includes both Self-initiated expatriates ( SIE's) and Assigned Expatriates(AE's). SIE's expatriates are Indian students who are studying in the UK and the AE's expatriates are the company assigned Indian full-time employees. Social support includes briefly the overall host country support provided for Indian expatriates in the host country. Social support is measured in three broader dimensions pertinent to Waxin cross-cultural adjustment model (2006), likely perceived organizational support, individual self-motivation, and contextual support, includes family support and host country environment. (Navas et al, 2005) classified six relevant contexts of acculturation of expatriates in a foreign country, which emphasize, politics and government, organizational work-related adjustments, economic perspective, family relations; social relations and ideology, which includes religious belief and customs. The structure of the thesis covers extensive theoretical part based on the intense review of literature in the field of expatriation, cross-cultural studies, information on this context about the United Kingdom and India and final part includes practical data analysis, business cases and recommendation for the future research.
Vedoucí práce: Zuzana Dvořáková
Disertační práce (Ph.D.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2017
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2017
Způsob přístupu: Internet
Keywords: podniková ekonomika a management [obor disert. práce]; disertace; dissertations